﻿Nonformal education for indigenous community in Indonesia: an initial review - Saripudin, Didin (Universiti Kebangsaan Malaysia, 2009)

(untitled)
﻿To fulfill each citizen's right in gaining equal education especially during the 9-year primary education, the National Education Department of Indonesia as developed two types of education -formal and nonformal education. Nonformal education is preferred by the indigenous learners because it is not too restrictive to the participants as it allows them to gain education while working to support their meagre living. This article discusses about the challenges faced by the indigenous communities in Indonesia, namely the Naga Village Society and the Sea People with respect to education and training. The study found that for the Naga Village people, the indigenous knowledge or local wisdom should be included in the school curriculum as part of an innovative move to develop the community. Apart from Sundanese as an indigenous content taught in the first grade, the Naga Village children are also being taught the skills to plait bamboo, farming and "pencak silat" (a form of martial arts). Similarly, the Sea children are having difJiculty with the formal arrangement in the learning process at the public school. The habit of wandering at sea has formed their attitudes and behaviours to adapt to their drifting environment that is usually influenced by wind movement and season. Formal schooling is not the only means to improve the quality of human resources and should not be forced on indigenous society. In nonformal education, the place of study does not necessarily be in a school building but it could be at home or on boat based on its environment. Besides the emphasis on 3R (reading, writing and arithmetic), the Sea children are being taught geometry, navigation, sea biology, oceanography, astronomy and fish processing -subjects that are relevant to their daily life.